Legal, economic, and environmental conditions for the application of “fee for discharging rainwater and snowmelt into waters” in Poland - Piontek, Wojciech (Economics and Environment, 2022)
This paper aims to identify and analyse the legal, economic and environmental conditions for the application of fees for discharging rainwater and snowmelt into waters. The article discusses the fundamental problems of rainwater management in Poland and the consequences of several decades of neglect. Economic and legal instruments used in water resources management are indicated. The fee for discharging rainwater and snowmelt to waters is characterised in detail. This paper shows the critical functions of the fee, legislative flaws, problems in practical application, factors determining the amount of the financial burden and potential measures for its optimisation. The directions of legislative changes, conditioning the fulfilment by the fee of the functions ascribed to it, have been indicated. This article is based on a review of the literature, legal acts, and statistical data from the Institute of Meteorology and Water Management and the Polish Central Statistical Office.